2020
DOI: 10.1038/s41598-020-74226-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical MRI and [18F]FDG PET/CT imaging of Schistosoma mansoni in a NMRI mouse model

Abstract: Schistosomiasis represents one of the most devastating worm parasitosis in the world. Current diagnostic methods are insufficient to determine the infection grade and the disease related organ damage. We herein investigated whether discrimination of infection grade and its correlation to liver damage could be accurately performed by multimodal imaging in a mouse model of Schistosoma mansoni infection. Therefore, groups of uninfected and infected mice underwent MRI and [18F]FDG PET/CT imaging. Anatomical MRI im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These cercaria are then discharged from the snail into the water, where they can infect the ultimate host once more, thus perpetuating the cycle (Fig. 1) (Lindner et al 2020).…”
Section: Schistosoma Life Cyclementioning
confidence: 99%
“…These cercaria are then discharged from the snail into the water, where they can infect the ultimate host once more, thus perpetuating the cycle (Fig. 1) (Lindner et al 2020).…”
Section: Schistosoma Life Cyclementioning
confidence: 99%
“…As early as 1950 physiology experiments demonstrated that schistosomes are large consumers of glucose [ 63 ]: therefore 18 F-FDG PET/CT imaging, as reported in a study with mice infected with S. mansoni , could be useful for the evaluation of worm burden in schistosomiasis infection [ 64 ]. Particularly noteworthy are also the results obtained in a study conducted by Lindner and collaborators, using mice infected with S. mansoni : the authors found a significantly higher uptake of 18 F-FDG in the spleen of infected mice in comparison to the control group, suggesting a possible role of splenic uptake in the determination of infection grade [ 8 ].…”
Section: Pet/ct Findingsmentioning
confidence: 99%
“…At this moment, the egg releases miracidia (the initial larval stage) which penetrates the intermediate host (aquatic snail) and undergoes several cycles of asexual reproduction, up to reaching the cercaria stage. Hence, cercaria is released by snail into the water, infecting again the final host [ 1 , 2 , 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation